Malaysian macroalga Padina australis Hauck attenuates high dose corticosterone-mediated oxidative damage in PC12 cells mimicking the effects of depression - Subermaniam, Kogilavani; Yow, Yoon Yen; Lim, Siew Huah; Koh, Ong Hui; Wong, Kah Hui (Elsevier, 2020)
Oxidative damage has been associated with the pathophysiology of depression. Macroalgae are equipped with antioxidant defense system to counteract the effects of free radicals. We explored the use of Malaysian Padina australis to attenuate high dose corticosterone-mediated oxidative damage in a cellular model mimicking depression. Fresh specimen of P. australis was freeze-dried and extracted sequentially with hexanes, ethyl acetate and ethanol. The extracts were screened for their phytochemical contents and antioxidant activities. Ethanol extract demonstrated the most potent antioxidant capacity and was selected for subsequent assays against high dose corticosterone of 600 µM-mediated oxidative damage in the rat pheochromocytoma (PC12) cells. The corticosterone reduced the cell viability, glutathione (GSH) level, aconitase activity, and mitochondrial membrane potential (MMP); and increased the lactate dehydrogenase (LDH) release, intracellular reactive oxygen species (ROS) level and apoptosis. However, the extent of oxidative damage was reversed by 0.25–0.5 mg/mL ethanol extract suggesting a possible role of P. australis-based antioxidants in the mitochondrial defense against constant ROS generation and regulation of antioxidant pathway. The effects were similar to that of desipramine, a tricyclic antidepressant. Our findings indicate that P. australis can be developed as a mitochondria-targeted antioxidant to mitigate antidepressant-like effects. © 2020 The Author(s)